Academic Administration of Basic Educational Institutions under Roi Et Primary Educational Service Area Office 2 - Hinsuy, Nonchai; Rooyuenyong, Wichain (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the current situation, the desirable conditions and needs, 2) to offer recommendation on academic administration of Basic Educational Institutions under Roi Et Primary Educational Service Area Office 2. The sample size was determined by using Taro Yamane table and stratified random sampling. The sample group consisted of 41 school administrators and 312 teachers with the total number of 353 people. The research tool was a questionnaire. The statistics by using frequency, percentage, mean standard and Modified Priority Needs Index (PNIModified) The research results were found that: 1. The current situation of academic administration of Basic Educational Institutions under Roi Et Primary Educational Service Area Office 2, in overall, was found that the practice was rated at a moderate level, when considering each aspect, it was found that the aspect with the highest average was development of educational institution curriculum, the aspect with the lowest average was research for educational quality improvement. The desirable conditions for academic administration, in overall, was at the highest level, when considering each aspect, it was found that the aspect with the highest average was assessment and evaluation, the aspect with the lowest average was research for educational quality improvement. The results of needs analysis (PNIModified) showed that academic administration of Basic Educational Institutions arranging from the highest to the lowest needs were as follows: 1) research for educational quality improvement, 2) development of educational media and technology, 3) assessment and evaluation, 4) development of quality assurance system and educational standards, 5) development of learning processes and 6) development of educational institution curriculum respectively. 2. Recommendations for academic administration of Basic Educational Institutions under the Office of the Roi Et Primary Educational Service Area 2 were as follows: 1) research for educational quality improvement, 2) development of educational media and technology, 3) assessment and evaluation, 4) development of quality assurance system and educational standards, 5) development of learning processes and 6) development of educational institution curriculum.